The Effect of Endurance and Leg Muscle Strength Training Method on the Increase of VO2Max - Dhuha, Ahad Agafian; Sulaiman, Sulaiman; Pramono, Harry (Journal of Physical Education and Sports, 2019)
VO2Max is the ability to breathe oxygen as much as possible during exercise. The objectives of this study were: to analyze the differences of the effect of continuous running and interval running exercises, to analyze differences of the effect between athletes with high and low leg muscle strengths, and to analyze the interaction of endurance training and leg muscle strength to increase VO2Max. Method: This study deployed a 2x2 factorial design, using pre-test and post-test. The population of the study is 44 athletes of Persatuan Drum Band Indonesia (Indonesian Drum Band Association) of Semarang. The sample of the study was 24 athletes selected through a purposive sampling technique. This current study consisted of two independent variables, which were manipulative and attributive variables, and one dependent variable. The instruments used were the Leg Dynamometer test and the Cooper Test. Results of the study: The training method Fvalue = 12.712 > 3.44 with a significance level of 0.05, leg muscle strength Fvalue = 0.992 < 3.44 with a significance level of 0.05, training method and leg muscle strength Fvalue = 0.535 < 3.44 with a significance level of 0.05. Conclusion: Endurance training method with interval running using low leg muscle strength is better than continuous running using low leg muscle strength. Trainers are suggested to use interval running to increase VO2MAX to obtain better endurance.